Alterations of functional connectivity of the motor cortex in Fabry disease: An RS-fMRI study. (9th May 2017) - Cocozza, Sirio; Pisani, Antonio; Olivo, Gaia; Saccà, Francesco; Ugga, Lorenzo; Riccio, Eleonora; Migliaccio, Silvia; Brescia Morra, Vincenzo; Brunetti, Arturo; Quarantelli, Mario; Tedeschi, Enrico
Abstract : Objective: To evaluate the presence of functional connectivity (FC) alterations of the motor circuits in patients with Fabry disease (FD) and their possible correlation with clinical variables with a resting-state (RS) fMRI analysis. Methods: In our cross-sectional study, 32 patients with FD with genetically confirmed classic diagnosis of FD (12 men, mean age 43.3 ± 12.2 years) were enrolled along with 35 healthy controls (HCs) of comparable age and sex (14 men, mean age 42.1 ± 14.5 years). RS-fMRI data were analyzed with a seed-based approach, with 2 different seeds for right and left motor cortex. Patients with FD underwent a clinical examination for the assessment of different motor functions. Correlations with clinical variables were probed with the Spearman correlation coefficient. Results: A reduction of FC was found in patients with FD compared to HCs between both motor cortices and 2 clusters encompassing, for each side, the caudate and lenticular nucleus ( p < 5 × 10 −4 and p < 10 −8 for right and left motor cortex, respectively) and between the left motor cortex and dentate nuclei ( p = 0.01) and Crus 1 in the right cerebellar hemisphere ( p = 0.001). No significant results emerged in tests for possible correlations of FC with clinical scores. Conclusions: An alteration of the corticostriatal pathway is present in FD, in line with the recently suggested subclinical involvement of motor circuits in this disease. These results shed new light on the pattern of cerebral involvement in FD.